Risco de consumo e qualidade nutricional de amendoim e paçoca, consumidos em Cascavel Paraná - Rosa, Talita Cristina Maffei da (2014)
Aflatoxins are products of secondary metabolism of Aspergillus sp. that appear after the phase of exponential growth of fungi and contaminate a wide variety of foods, especially peanuts. Due to the carcinogenic, mutagenic and teratogenic effects, aflatoxins deserve special attention from the food industry, because they represent a risk to human health, thus it is necessary to develop control measures during the process of food production, as well as in farming, harvest, storage and transportation. Whereas peanuts and derivatives products are widely consumed, this study aimed to evaluate, in the city of Cascavel, state of Paraná, the occurrence of aflatoxins in peanuts and derivatives, the potential risk of human exposure to these mycotoxins, and the food safety and nutritional quality these products offer. First, a survey of consumption of peanuts and derivatives by the population of Cascavel PR was conducted through a structured questionnaire. 40 lots of peanut and peanut candy called paçoca were collected in five supermarkets, being half of the lots expiration date one month ahead, and the other half expiration date four or five months ahead. Physical, chemical, microbiological and determination analyzes of aflatoxins were performed. The results suggest that the shelf life of the peanut does not interfere in their nutritional quality; but it interferes in the peanut candy nutritional quality, as protein and lipid levels decrease. It was shown that all the samples of peanuts and peanut candy were contaminated with fungi, with an average of 7,24 and 3,13 UFC.g-1 x 103 to peanuts and peanut candy due to expire in one month, and 4,93 and 4,08 UFC.g-1 x 103 to new peanuts and peanut candy, respectively; especially the peanut near the expiration date was contaminated. The analysis showed high aflatoxin contamination in some lots of peanut and low contamination in peanut candy, with average of 36,15 and 0,21 μg.Kg-1 for peanuts and peanut candy due to expire in one month, and 32,74 and 0,28 μg.Kg-1 for new peanuts and peanut candy, respectively. Risk analysis indicated medium daily intake results for aflatoxins in peanuts and low daily intake for peanut candy. These two products offer a risk to population, as they are genotoxic substances that can cause harm to the consumer health.